Effect of preoperative treatment strategies on the outcome of patients with clinical T3, non-metastasized rectal cancer: A comparison between Dutch and Canadian expert centers. Issue 8 (August 2015) - Breugom, A.J.; Vermeer, T.A.; van den Broek, C.B.M.; Vuong, T.; Bastiaannet, E.; Azoulay, L.; Dekkers, O.M.; Niazi, T.; van den Berg, H.A.; Rutten, H.J.T.; van de Velde, C.J.H.
Abstract Aim High-dose-rate brachytherapy (HDRBT) appears to be associated with less treatment-related toxicity compared with external beam radiotherapy in patients with rectal cancer. The present study compared the effect of preoperative treatment strategies on overall survival, cancer-specific deaths, and local recurrences between a Dutch and Canadian expert center with different preoperative treatment strategies. Patients and methods We included 145 Dutch and 141 Canadian patients with cT3, non-metastasized rectal cancer. All patients from Canada were preoperatively treated with HDRBT. The preoperative treatment strategy for Dutch patients consisted of either no preoperative treatment, short-course radiotherapy, or chemoradiotherapy. Cox proportional hazards models were used to estimate hazard ratios (HR) with 95% confidence intervals (CIs) comparing overall survival. We adjusted for age, cN stage, (y)pT stage, comorbidity, and type of surgery. Primary endpoint was overall survival. Secondary endpoints were cancer-specific deaths and local recurrences. Results Five-year overall survival was 70.9% (95% CI 62.6%–77.7%) in Dutch patients compared with 86.9% (80.1%–91.6%) in Canadian patients, resulting in an adjusted HR of 0.70 (95% CI 0.39–1.26; p = 0.233). Of 145 Dutch patients, 6.9% (95% CI 2.8%–11.0%) had a local recurrence and 17.9% (95% CI 11.7%–24.2%) patients died of rectal cancer, compared with 4.3% (95% CI 0.9%–7.5%) local recurrences and 10.6% (95% CI 5.5%–15.7%) rectal cancer deaths out of 141 Canadian patients. Conclusion We did not detect statistically significant differences in overall survival between a Dutch and Canadian expert center with different treatment strategies. This finding needs to be further investigated in a randomized controlled trial.